Financial and Legal Prospects for the Use of Government Bond Loans in Modern Conditions - ZHMURKO, Irina M. (Journal of Advanced Research in Law and Economics; Vol 10 No 3 (2019): JARLE Vol X Issue 3(41) Summer 2019DO - 10.14505//jarle.v10.3(41).37, 2019)
The purpose of the study is to identify positive aspects of expanding the use of government bond loans. The paper also focuses on theoretical concepts of the ratio of taxes and loans, analyzing the advantages and disadvantages of government bond loans to determine their impact on the decisions of the issuer and the investor. Consideration of foreign experience in the use of bond loans allows identifying common features and aspects to improve the legal regulation of this institution in Russia science and practice. The results of the research consist of summarizing the studied material and describing the prospects for the development and use of government loans as a tool of financial and legal policy. The experience of foreign countries proves that it is possible to determine the legal nature of a government bond loan through the prism of regulating a new institution – the issue obligation. Conclusion: it is advisable to adopt a normative legal act that would systematize the form of government debt, contain general rules for the use of certain types of borrowing and mechanisms for servicing and repayment of debt, and provide other guarantees, principles of compensation, ways to restructure debt obligations, as well as a mechanism for interaction of public authorities in this area with clear regulation of the powers of public authorities and sanctions for late performance or non-performance by the issuer of its obligations.